Analysis of volatile components in different broken rice by HS‐SPME/GC‐TOFMS. (19th February 2023) - Peng, Kaixiong; Tang, Qunyong; Zheng, Yuhan; Ji, Fang; Chen, Xiaoming
Abstract: In this study, headspace solid‐phase microextraction (HS‐SPME) combined with gas chromatography‐time‐of‐flight mass spectrometry (GC‐TOFMS) was used to detect and analyse the volatile components of five samples with different degrees of fragmentation, combined with cluster analysis, orthogonal partial least squares discrimination analysis (OPLS‐DA) and relative odour activity value (ROAV) analysis. The results showed that 70 volatile components were detected and identified in samples with different degrees of fragmentation. 40 were co‐containing components. Cluster analysis revealed a high degree of similarity between samples B (20 mesh sieve top) and C (40 mesh sieve top), which were grouped into one category. The order of variation in the relative content of volatile components was A (unbroken) > E (120 mesh sieve top) > D (80 mesh sieve top) > B. C; the OPLS‐DA analysis revealed significant differences in the volatile composition of rice samples with different degrees of fragmentation, This variation between samples is mainly due to the relative content of volatile components of 36 projections of variable importance (VIP > 1), such as ethyl butyrate, ethyl phenylacetate, and dimethyl trisulfide. A total of 12 volatile components with ROAV > 1, including ethyl hexanoate, 2‐acetyl‐1‐pyrroline, and E ‐2‐nonenal, were found to be the key volatile components in five samples based on their ROAV, the different degrees of crushing had a greater impact on the overall aroma of the rice, and the results can be used as a reference for further rice processors. Abstract : HS‐SPME/GC‐TOF MS was used to analyse the differences of volatile components in rice with different crushing degrees, which provided flavour reference for rice and further processed food.